Retear of anterior cruciate ligament grafts in female basketball players: a case series - Tanaka Yoshinari; Yonetani Yasukazu; Shiozaki Yoshiki; Kitaguchi Takuya; Sato Nozomi; Takeshita Shinya; Horibe Shuji (BMC, 2010)
Abstract Background Incidence of anterior cruciate ligament (ACL) injuries in young female basketball players is higher than that in male basketball players. Graft retears are more frequent with the increasing number of ACL reconstructions. The present study aimed to examine the incidence of retears in competitive female basketball players. Methods Sixty-four female basketball players (aged 12 to 29 years) who underwent primary anatomic double-bundle ACL reconstruction using hamstring grafts participated in the study. We investigated incidence, mechanism, and patient characteristics of ACL graft retears. Mann-Whitney U test was used for statistical analysis, and the level of significance was determined at P < 0.05. Results Six patients suffered from ACL graft retear (9.4%). Mean duration between primary ACL reconstruction and incidence of retears was 11.7 months. However, there were no other postoperative graft ruptures after 24 months. Primary injury and retear mechanisms varied by patient. At six months after the primary ACL reconstruction surgery, mean quadriceps and hamstring strengths were 81% and 87%, respectively, indicating favorable recovery of muscle strength. However, preoperative quadriceps and hamstring strength in the retear group were 65% and 71%, respectively. In particular, preoperative quadriceps strength in the retear group demonstrated a lower value than that in the uninjured group (P < 0.05). Conclusions We observed a high incidence of ACL graft retears in competitive female basketball players, as previously reported. Considering the timing of graft retear occurrences, an early return to playing basketball should be avoided following ACL reconstruction. Closer attention should be paid to player preoperative condition, as well as muscle strength and postoperative status.